Peningkatan Daya Saing UKM Rotan Indah Jepara Menuju Pasar Sasaran Ekspor - A Khoirul Anam; Miftah Arifin; Anna Widiastuti; Zainul Arifin (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
Rattan craft is one of the regional superior products in Jepara. Because the products have high quality, they are able to compete in the international market. However, the presence of rattan handicrafts also experienced ups and downs, both at local, national and international trade. Therefore, it is necessary to increase the competitiveness of rattan craftsmen through a mentoring program from the service program at SME of Rotan Indah Jepara. The strategic value of the assisted partner is increasing competitiveness towards the export market through approaches to the application of appropriate science and technology, enhancing the quality and quantity of production, and strengthening institutional capacity. The achievement of the target shows the accuracy of the assistance method used. Several programs have been carried out, including strengthening production equipment and implementing appropriate technology, strengthening product capacity and quality, strengthening marketing capacity, and strengthening corporate governance, compiling accounting systems and computerized financial reporting. The results of this program show that all the targets can be realized. The impact and benefits of this service program are social changes, effectiveness and increased productivity, in the form of increased sales turnover, changes in better work patterns, increased production capacity due to changes in work patterns, systems and technology used. Another added value is shown to be significant savings from good management patterns and more efficient production processes.